An Analysis of Addiction for Violent Online Game in Adolescent: Virtual Ethnography - Seenivasan, R. (Gyan Management Journal, 2019)
"Addiction" and "Gaming problem” began to appear in the literature to describe those who spent excessive amounts of time online that interfered with other life activities. In previous decade, researchers have been trying to prove that online video games are bad. Much of the attention has focused on the violent content of some of the games, and many dozens of studies have been done in attempts to prove that playing online violent games causes real-world violence. For all of these reasons, people have lots of questions surrounding what science says about the effects of video games. Do games cause violence or aggression? Are they addictive? Are they healthy ways to relax and de-stress? Using virtual ethnography for psychological and social problems in adolescent. The paper is intended primarily for parents and those who work with young people who may be obsessed with online video games.